Model Pembelajaran RADEC (Read, Answer, Discuss, Explain, and Create) Ditinjau dari Perspektif Pembentukan Profil Pelajar Pancasila - Nursida Sutantri; Wahyu Sopandi; Wawan Wahyu; Abdul Latip (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2023)
The independent curriculum policy emphasizes the development of the Pancasila student profile students through the learning process carried out by teachers and students. This study aims to describe the application of the RADEC learning model in chemistry learning to form a profile of Pancasila students in students. This study uses a qualitative descriptive approach involving one teacher and 34 students of class XII MIPA who carry out learning chemistry for voltaic cells. The research instrument was an observation sheet on the appearance of the Pancasila student profile, which the observer used as a reference in observing the learning process. The results showed that, in general, the profiles of Pancasila students, namely Faith and Faith in God Almighty and Noble Morals, Global Diversity, Mutual Cooperation, Independent, Critical and Creative Reasoning, were identified to have increased from the first meeting to the fourth meeting of learning and the syntax of the RADEC learning model could facilitate the formation and development of student profiles of Pancasila according to the characteristics of the characters and types of learning activities. The results of this study indicate that the RADEC learning model is one of the learning models that teachers can implement when viewed from the perspective of forming a Pancasila student profile.